Implementation of Customer Relationship Management (CRM) Strategy in Increasing the Loyalty of Non-Pawn Customers at PT Pegadaian Lempuyangan Branch - Sarah Nur Fadhilah; Agus Abdurrahman (Finance : International Journal of Management Finance, 2024)
Economic activities in each country are closely related to financial issues. In the pawn and credit sector, there is very tight competition at the moment, this is also realized by PT Pegadaian Lempuyangan Branch. Therefore, the company's focus must be increased in increasing customer loyalty and delivering value. The purpose of this writing is to determine the increase in non-pawn customer loyalty at PT Pegadaian Lempuyangan Branch resulting from the implementation of the Customer Relationship Management (CRM) strategy. The qualitative method was chosen as the method used in this writing. The data collection techniques involved in this writing are in the form of observations and interviews with internal and external parties of the company. The data that has been collected will then be analyzed using content analysis techniques. As a result, Customer Relationship Management was found to have a significant and real impact on customer loyalty, especially in owning the products offered by the company. Customer Relationship Management is very important to maintain added value and ensure the company's survival. In implementing Customer Relationship Management to increase customer loyalty, companies need to consider customer needs when making product offers, especially non-pawn products. This can be done by increasing the use of social media platforms for offers and improving the service features available on the Pegadaian Digital application for transaction services.